Docosahexaenoic acid inhibits Ca2+ influx and downregulates CaSR by upregulating microRNA‐16 in pulmonary artery smooth muscle cells. Issue 11 (13th July 2020) - Liu, Jin‐jun; Tang, Ming‐ming; Zhu, Ming‐li; Xie, Cai‐xia; Kang, Pin‐fang; Ling, Xuan; Zhang, Heng; Wang, Xiao‐jing; Tang, Bi
Abstract: Docosahexaenoic acid (DHA) is reported to have the potential to ameliorate pulmonary arterial hypertension (PAH), while the specific mechanism is still obscure. This study aims to investigate the function of DHA in pulmonary artery smooth muscle cells (PASMCs) and explore the underlying mechanism. In our study, DHA was used to incubate PASMCs. Cytosolic‐free Ca 2+ concentration ([Ca 2+ ]cyt) was measured using Fluo‐3 AM method. Real‐time polymerase chain reaction was used to detect microRNA‐16 (miR‐16) and calcium‐sensing receptor (CaSR) messenger RNA expression levels. CCK‐8 assay, BrdU assay, and Transwell assay were employed to detect the effects of DHA on proliferation and migration of PASMCs. CaSR was confirmed as a direct target of miR‐16 using dual‐luciferase assay, polymerase chain reaction, and Western blot analysis. It was found that DHA significantly inhibited PASMC proliferation and migration and decreased [Ca 2+ ]cyt. After transfection of miR‐16 mimics, proliferation and migration ability of PASMCs were significantly inhibited, whereas opposite effects were observed after miR‐16 inhibition. [Ca 2+ ]cyt was also inhibited by miR‐16 transfection. DHA then promoted the expression of miR‐16, and the effects of DHA on PASMCs were annulled when miR‐16 was inhibited. CaSR was identified as a direct target of miR‐16. CaSR was inhibited directly by miR‐16 and indirectly by DHA. In conclusion, DHA inhibits the proliferation and migration of PASMCs, and probably ameliorates PAH via regulating miR‐16/CaSR axis.